Impact of Microfinance on Poverty Alleviation: A Study in the Southern Part of Bangladesh - Badiuzzaman; Uddin, Md. Hasan; Hossain, Afjal (Asian Business Review, 2020)
Poverty is the incapability of a person to meet his basic need like food, cloth, and shelter. Every country has to face poverty across the world. Bangladesh has also been suffering from poverty. Micro Finance Institutions in Bangladesh are trying to reduce the poverty alleviation over the country. The purpose of this study is to identify the impact of different microfinance services to poverty reduction in Bangladesh. A structured questionnaire was used to collect the data from respondents in Barishal division, Bangladesh, and OLS regression was estimated to find out the impact of microfinance services to the poverty reduction in Bangladesh. Results show that micro-credit mostly influences poverty reduction. Savings, micro-insurance, and training also influence the poverty reduction in Bangladesh. The implication of the study is that microfinance service provisions should be more user-friendly for the customers so that the services can be advanced to the locals of the different regions of Bangladesh for facilitating the rapid economic growth. Financial education may be introduced for a better understanding of microfinance services collection, usage, and for return policy. Policymakers may also provide some guidelines to fight poverty for their rest of life.